2020
DOI: 10.1021/acs.joc.9b02876
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanochemical Zinc-Mediated Barbier-Type Allylation Reaction under Ball-Milling Conditions

Abstract: A Ball-milling enabled zinc-mediated Barbier-type allylation reaction is reported. Notably runnning the reaction in this manner renders it effective irrespective of the initial morphology of the zinc metal. The process is operationally simple, does not require inert atmospheres or dry solvents and is reported on a range of aldehyde and ketone substrates, a gram scale process is demonstrated.Zn flake (325 mesh, 2.0 equiv.)DMSO (1.0 equiv.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 73 publications
0
26
0
Order By: Relevance
“…This strategy clearly simplifies the synthetic route toward organozinc species for example in the Negishi cross‐coupling reaction by avoiding derivatization of the substrates through classical transmetalation steps (Scheme 9a) [163] . The application of this mechanochemical approach has also led to more sustainable versions of classic C−C bond formation protocols such as the Reformatsky reaction [164a] and the Barbier‐type allylation reaction [164b] …”
Section: Mechanochemistry and The Twelve Principles Of Green Chemistrymentioning
confidence: 99%
“…This strategy clearly simplifies the synthetic route toward organozinc species for example in the Negishi cross‐coupling reaction by avoiding derivatization of the substrates through classical transmetalation steps (Scheme 9a) [163] . The application of this mechanochemical approach has also led to more sustainable versions of classic C−C bond formation protocols such as the Reformatsky reaction [164a] and the Barbier‐type allylation reaction [164b] …”
Section: Mechanochemistry and The Twelve Principles Of Green Chemistrymentioning
confidence: 99%
“…Barbier-type allylation has been the traditional approach to the synthesis of trifluoromethyl-and allylsubstituted tert-alcohols (Guo et al, 2017;Nie et al, 2011;Tordeux et al, 1990). The Barbier process involves the introduction of metal complexes, such as indium (Araki et al, 1988;Loh et al, 1999;Roy and Roy, 2010;Shen et al, 2013), zinc (Grellepois et al, 2017;Metzger et al, 2010;Yin et al, 2020), ruthenium (Cicco et al, 2017;Wang et al, 2017Wang et al, , 2021, titanium (Li et al, 2020), or mercury (Cao et al, 2016;Gong et al, 2019), into the carbon-halide/carbon-silyl bond for generating the reactive nucleophilic allylmetal intermediates, which react with the trifluoromethyl ketone to furnish the trifluoromethyl-and allyl-substituted tert-alcohol (Figure 1a). Despite these advantages, the Barbier reaction requires stoichiometric amounts of metals, and catalytic approaches are limited to the use of allylboron/allylsilane reagents that are difficult to prepare.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, liquid-phase reactions are characterized by using bulk toxic organic solvents and harsh reaction conditions. With the need for cleaner, safer, and more sustainable chemical transformations, the use of mechanochemistry, which is identified by IUPAC as one of the 10 world-changing technologies [ 1 ] in chemical synthesis, has boomed over the past few decades and is rapidly becoming a powerful tool for environmentally friendly and sustainable synthesis of molecules and materials, including coordination, supramolecular, and covalent structures [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical ball-milling technique, an eco-friendly mechanochemical protocol, can not only promote solvent-free reactions and increase the reaction efficiency [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ], even more attractively, but also alter chemical reactivity and selectivity compared to the solution-based counterparts, leading to different products, which draws forth the tantalizing hypothesis that some molecules can only be obtained by mechanochemistry [ 13 , 14 ]. For instance, Wang et al reported the reaction of [60]fullerene (C 60 ) and KCN under high-speed vibration ball milling (HSVM) for 30 min to unexpectedly afford fullerene dimer C 120 even after quenching with trifluoroacetic acid (TFA) [ 15 ], while the same reaction in a mixture of 1,2-dichlorobenzene (ODCB) and N , N -dimethylformamidal (DMF) reported earlier by Wudl and coworkers afforded a different fullerene product, C 60 H(CN) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%